Performance Analysis Of Single-Phase Induction Motor Using 14-Pole Rotor For Ceiling Fan Application - Amran, Muzzammil (Universiti Sains Malaysia, 2017)
Single-phase induction motor has been used for a long time for trivial and repetitive chores due to its simplicity in construction and easy availability of single-phase power supply in almost every household. They are robust, relatively cheap, high efficiency and almost free maintenance. Therefore, it is often used in light-duty industrial applications where three-phase supply is not readily available. Ceiling fans are one of the popular applications often used in Malaysia for cooling and ventilation purpose. The purpose of this project is to make an improvement by analyzing the performance of ceiling fan motor. The design and model are the important thing to create by using finite element method (FEM). There are two types of analysis conducted to study the performance i.e. steady-state AC analysis and rotational motion analysis. Both analyses can be implemented in FEM software. All FEM models are built and simulated to calculate and record the input current, input power, power factor and output torque. The phase difference between the input voltage, main and auxiliary currents of the motor and also the efficiency of the motor can be accurately predicted. Different motor designs that have different angular velocity and values of the capacitor varied from 1.8μF, 2.0μF and 2.5μF in rotational motion analysis. All information obtained are compiled and analyzed. The greater the value of the capacitor, the greater the input power required and output torque. Designed motor with capacitor value of 2.0μF shows the best performances.